(untitled) ("Conference on Universal Science Research 2023", 2026)
This article scientifically analyzes the effect of psychological stress on the cardiovascular system. In a state of stress, an increase in hormones such as cortisol and adrenaline in the body causes changes in blood pressure, heart rate, and vascular tone. As a result of prolonged stress, chronic pathologies such as ischemic heart disease, hypertension, and arrhythmias can develop. The article also highlights the effectiveness of psychological approaches - meditation, breathing exercises, positive thinking, and psychotherapy - in improving heart health by reducing stress. The results of the study show that psychological stability is an integral part of medical prevention and plays an important role in preventing heart disease.